2015
DOI: 10.1155/2015/341616
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Measurement and Interpretation of the Changes of Physical Properties after Heat Treatment in Tight Porous Media

Abstract: Prevention of water blocking and optimization of multiscale flow channels will increase gas production of tight reservoirs. Physical properties of samples from representative tight gas reservoirs were measured before and after high temperature treatment. Results show that, with the increase of treatment temperature, mass decreases, acoustic transit time increases, and permeability and porosity increase. Permeability begins to increase dramatically if treatment temperature exceeds the threshold value of thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…For conventional gas reservoirs, single hydraulic fracturing mainly generates great-scale fractures from the preexisting fractures. However, the reserves for tight gas reservoirs mainly exist in micro-scale pores [8]. Therefore, maintaining high gas production for the long term mainly depends on the release of gas stored in the matrix through some special techniques [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…For conventional gas reservoirs, single hydraulic fracturing mainly generates great-scale fractures from the preexisting fractures. However, the reserves for tight gas reservoirs mainly exist in micro-scale pores [8]. Therefore, maintaining high gas production for the long term mainly depends on the release of gas stored in the matrix through some special techniques [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In their experimental study, the shale obtained from the Shanggu basin of Shangxi, China, was burned in an air environment at a temperature of 800 • C for 45 min to oxidize the organic matter and improve the physical properties of the shale. Kang et al [1,8] investigated the change of porosity in the shale samples under a high temperature condition, up to the target temperature of 800 • C. They suggested that the application of FHT must be combined with multi-stage hydraulic fracturing in horizontal wells. The experience of Jamaluddin et al [18] had great significance as a reference.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations